Evaluation of Soil Physical/Chemical Parameters for Agriculture Production in Vaijapur Taluka Using VNIR-SWIR Reflectance Spectroscopy - Bhise, P.R; Kulkarni, S.B (International Journal of Computer Sciences and Engineering, 2018)
Soil is a precious resource of the environment to survival and humanistic welfare .From the mixture of minerals, organic matter and living organism components soil is formed. Soil Physical, Chemical and Biological characteristics plays a very significant role in agricultural field. Accelerated low cost and predictable assessment of soil quality under agricultural management is necessary to accomplish convenient observation of the effects of various management practices on soil conditions to avoid soil degradation and ensure feasible soil productivity and also soil security. The objective of this study is to find soil Physical and Chemical parameter contents from top surface (0-20cm) of agricultural soil in Vaijapur taluka. We measure raw spectral reflectance of all soil samples .and also use 1st and 2nd Derivatives techniques for pre-processing spectral data. Mostly soil texture of Vaijapur taluka comes under the clay loam. In this study we predicting soil properties with particular sensitive band such as soil water(1400 nm, 1900 nm, 2200 nm),pH (1477nm,1932nm and 2200 nm),Sand(1900 nm),Silt(2000 nm),Clay(2200 nm) and for Soil Organic Matter(750-1000nm) for better crop production in Vaijapur taluka using Field Spec4 Spectroradiometer between 350-2500 nm wavelength. It is a rapid, non-destructive, and cost-effective and time consuming tool for evaluating the soil parameters. According to R-square and RMSE values the PLSR model gives better results to achieve these objectives and here we also suggest crops which is suitable for soil in Vaijapur taluka.